Validation of expression stability of reference genes in response to herbicide stress in wild oat (Avena ludoviciana) - Akbarabadi, Ali; Ismaili, Ahmad; Kahrizi, Danial; Nazarian Firouzabadi, Farhad (Cellular and Molecular Biology, 2018)
Weeds are serious problem in crop production and wild oat is a grass weed of economic and agronomic significance. We need to extend our basic knowledge of weeds especially in molecular genetics and gene expression. For study of gene expression by semi-quantitative and quantitative PCR, it is recommended that normalization of reference genes be carried out in order to select the most stable reference gene for a precise gene expression study. The purpose of this research was evaluation of four reference genes in response to treated and untreated (control) by herbicide in two tissues (stem and leaf) of non-target site resistance wild oat (A. ludoviciana). Four candidate reference genes including Actin, Ef1Î± (elongation factor 1 alpha), GAPDH (glyceraldehyde 3-phosphate dehydrogenase) and TBP (TATA-box-binding protein) were used to determine stable reference gene exposed to the herbicide using the statistical methods of NormFinder, BestKeeper and delta-Ct. NormFinder indicated that TBP and Actin genes are the best combination of two genes for normalizing calculations (with a combined gene stability value of 0.012) for qPCR analysis under herbicide stress in different tissues of non-target site resistance wild oat. Based on the statistical results, the Ef1Î± gene was identified as the unstable reference gene. Totally, according to results of this study, TBP gene is the most stable reference gene and therefore, this gene can be used as a reference gene for future studies of quantitative PCR analysis of herbicide stress-responsive gene expression in wild oat and potentially in other grass weed species.